Heat Transfer Simulation on the Wall of Rotary Cast Iron Smelting Furnace Capacity of 1 ton/hour - Amir Syam; zulfikar zulfikar; Muhammad Idris Hutasuhut (Universitas Medan Area, 2018)
The rotary smelting furnace is a cast iron smelting furnace with the working principle of raw material rotated in a melting drum. The difficulty of this type of furnace is if the furnace wall is damaged, it will be very difficult to determine the appropriate conduction coefficient material as a replacement material. Numerical simulations are required to obtain the heat transfer information that occurs on the furnace wall. This analysis aims to (1) obtain the temperature distribution occurring in the furnace wall, and (2) obtain the heat transfer coefficient on the wall surface on the inside, center, and outside of the melting furnace. Calculation of numerical simulation in this research is assisted by using Ansys software. The theoretical basis of numerical heat transfer simulation analysis can be determined by using the conduction temperature equation in each node. The load conditions in this case are assumed as thermal loads. The result obtained temperature distribution on the inner wall is 1590 oC, middle 1470 oC, and outside 1104 oC.